First photographic record of Red-breasted Parakeet Psittacula alexandri (Linnaeus, 1758) (Psittaciformes: Psittaculidae) from Haryana state in India - Aruna Yadav; Deepak Rai; Piyush Goyal; Anju Anju; Ritu Pal Bhura; Ashish Kumar Arya (Rivista Italiana di Ornitologia - Research in Ornithology)
Haryana is a state in northern India, situated in the Indo-Gangetic Plain. The single female individual of Red-breasted Parakeet Psittacula alexandri was observed on 23 November 2023 in the Kurukshetra University Campus, and its observation was presented as the first photographic record from the state of Haryana. The survey was also targeted to record and observe the species activity, interaction with other bird species, and nesting pattern. The presence of a single female individual of the Red-breasted Parakeet is primarily observed to be an example of a vagrant sighting of this bird. It is a near-threatened species and shows a global declining population trend. Addressing the pet trade and enforcing strict regulations on the import of faunal species are imperative in this regard. Public education regarding non-native species and their effects on ecosystems is also necessary.